Pengembangan Video Pembelajaran Multimedia menggunakan Canva pada Pembelajaran Pendidikan Pancasila Kelas 4 SDN Sukamaju - Dechika Nuhasetia Hidayat; Rana Gustian Nugraha; Enjang Yusup Ali (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The research was conducted based on findings in the field that teachers were not yet fully using innovative and creative learning media in the classroom during learning. The rapid development of science and technology is a challenge for learning in the 21st century, because it must involve the help of technology in the field of education. Lack of use of media makes students easily bored, unenthusiastic and difficult to understand the material. One learning media that is interesting and keeps up with the times is by using multimedia learning video media. Using Canva can overcome difficulties in the 21st century. This development aims to produce a learning media product and describe the feasibility of developing multimedia learning videos using Canva on cultural diversity material in elementary schools. The type of research used in this research is research and development (R&D). The research and development design model used is the ADDIE development model. The ADDIE research model is a model that involves a procedure with five steps which include Analysis, Design, Development, Implementation, and Evaluation. Based on the validation results, the material expert received a "very good" qualification. Media results validated by media experts qualify as "very good" and language results validated by linguists qualify as "very good" and are suitable for use in class IV at SDN SukaMaju. The results of student responses from individual group product testing, small group product testing and large group product testing were "very good" feasibility.